PENGARUH AUDIT OPERASIONAL, PENGENDALIAN INTERNAL, DAN MOTIVASI KERJA TERHADAP EFEKTIVITAS PELAYANAN KESEHATAN DI RUMAH SAKIT (Studi Empiris Pada Rumah Sakit Umum Daerah Bangkinang, Kabupaten Kampar) - Atika, Amaliah; Andreas, Andreas; Al, L Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This purpose of this research are to test and analyze the Influence of Operational Audit, Internal Control and Work Motivation on the Effectiveness of Health Services in hospitals. The population in this study was employees working at Bangkinang Regional General Hospital in Kampar. The sample in this study was 85 employees from the general administration, finance, human resources and education, medical services and SPI at the hospital in Kampar selected using a Slovin formula. The study used primary data by disseminating questionnaires. The method of analysis used in this study is multiple regression analysis. The analysis tool used in this study is Stastistical Product and Service Solution (SPSS) version 21.0 for windows. The results of this research indicate that: (1) operational audits have a significant effect on the effectiveness of health services, (2) internal control significantly affects the effectiveness of health services, and (3) work motivation significantly affects the effectiveness of health services.Keywords : Operational Audit, Internal Control, Work Motivation, Effectiveness of Health Services.